Brainstem Injury from Perinatal Asphyxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The clinical, radiological and neuropathological features of selective hypoxic-ischemic injury of the brainstem with relative sparing of cortex and subcortical white matter in an asphyxiated term infant are described in a case reported from the Division of Neurology and Depts of Pediatrics, Pathology and Radiology, British Columbia's Children's Hospital, Vancouver, Canada.